2006
DOI: 10.1097/00000542-200609000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Pharmacology of Intrathecal Granulomas

Abstract: Intrathecal opiate-induced granulomas are not strictly dependent on opioid receptor activation. Therefore, opiates at equianalgesic doses present different risks for granuloma formation. Importantly, D/L- and D-methadone also resulted in parenchymal necrosis, an affect associated with the N-methyl-D-aspartate antagonist action of the D-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 29 publications
0
84
1
Order By: Relevance
“…For opiates, the manifestation of this toxicity is the intrathecal granuloma [37, 116, 461-463]. Our group showed that the primary determinant for intrathecal opiate granulomas is the local concentration to which the tissue adjacent to the catheter tip is exposed [49, 51, 52]. Even baclofen, which has no strong evidence of granuloma formation in humans, may have limitations in that regard 
if concentrations higher than the currently available formulation (2mg/mL) is employed ([464] but see [267]).…”
Section: Current Spinal Agentsmentioning
confidence: 99%
“…For opiates, the manifestation of this toxicity is the intrathecal granuloma [37, 116, 461-463]. Our group showed that the primary determinant for intrathecal opiate granulomas is the local concentration to which the tissue adjacent to the catheter tip is exposed [49, 51, 52]. Even baclofen, which has no strong evidence of granuloma formation in humans, may have limitations in that regard 
if concentrations higher than the currently available formulation (2mg/mL) is employed ([464] but see [267]).…”
Section: Current Spinal Agentsmentioning
confidence: 99%
“…32 Systematic studies suggested that the risk of granuloma formation is correlated with local CSF concentrations. 33 Interestingly, sampling lumbar CSF in dogs proximal to the catheter tip have shown in acute pharmacokinetic studies that at the 12 mg/ml/day dose, CSF concentrations were on the order of 42,000 ng/mL. 13 Interestingly, we emphasize that in the present case, the patient displaying the granuloma received a daily dose of 36 mg/day.…”
Section: Changes In Drug Delivery and Csf/plasma Concentrationsmentioning
confidence: 59%
“…Veizi et al demonstrated that doses of monotherapy opioids may increase on the order of 535 ± 180% within 12 months of initiation [7]. With dose escalation comes increased intrathecal concentrations, creating concern for granulomas, non-infectious collections of cells around the catheter site [8]. To improve patient outcomes and safety, a group of expert physicians was convened to standardize approached to intrathecal therapy.…”
Section: On Label Medicationsmentioning
confidence: 99%
“…Historically defined, intrathecal therapy has challenges, including impacts on hormonal balance, space occupying granuloma, opioid dose escalation, platform inefficiencies, and limited agents that are Food and Drug Administration (FDA) labeled for this use [2, 5-8]. Importantly, intrathecal therapy requires a platform to deliver a medicine; it does not define the medicine employed.…”
Section: Introductionmentioning
confidence: 99%